Pengaruh Dosis Inokulum Marasmius sp. dan Lama Inkubasi terhadap Kandungan Komponen Serat dan Protein Murni pada Sabut Kelapa Sawit untuk Bahan Pakan Ternak - Endri Musnandar (Fakultas Peternakan Universitas Jambi, 2006)
The objective of the experiment was to find out the best inoculum dosage and incubation time for fiber component percentage and true protein percentage. The experiment was arranged by a Completely Randomized Design with factorial pattern 4x4, which the first factor was inoculum dosage (D2,5=2,5%; D5=5%; D7,5=7,5%; and D10=10%) and the second factor was incubation time (W1=1 week, W2= 2 week, W3 = 3 week, and W4= 4 week), the treatment combination were replicated 3 times which component fiber percentage and true protein percentage as parameters. All data were analyzed by analysis of variance followed DMRT. The results of experiment showed that there was significant interaction between inoculum dosage and incubation time on fiber component and true protein percentage. The lowest of fiber component especialy lignin and highest true protein percentage were found at D3W3 combination treatment, which the fiber componen percentage was NDF (67.63%), ADF (60.50%), selulosa (45.27%), lignin (9.93%), and True protein (8.957%).